ERAN KUALITAS PRODUK TERHADAP KEPUASAN PEMBELI KORAN SUARA MERDEKA SEMARANG - Cahyani, Alya Takwarina (Proceeding SENDI_U, 2020)
The purpose of this study was to determine the effect of marketing communication and product quality onthe satisfaction of Suara Merdeka Semarang buyers. The type of research used is explanatory research. Datacollection using tools such as questionnaires and Google forms using purposive sampling techniques. Thesample used was 100 respondents who had been selected with the specified criteria. The methodology used toanalyze primary data in this study is to use validity, reliability, coefficient of determination, F test, and linearregression with the help of the IBM SPSS version 24 program. The results showed that marketingcommunication and product quality to the satisfaction of Suara Merdeka Semarang buyers. Product quality hasa greater influence on the satisfaction of Suara Merdeka Semarang buyers compared to marketingcommunications on the satisfaction of Suara Merdeka Semarang buyers